Emergent Crisis of COVID-19 Pandemic: Mental Health Challenges and Opportunities - Radfar, Amir; Ferreira, Maria M.; Sosa, Juan P.; Filip, Irina (Frontiers in Psychiatry, 2021)
Mental health is a fundamental human right and is part of the wellbeing of society. The public health burden of mental health disorders affects people's social and economic status around the world. Coronavirus's (COVID-19) negative impact on the economy and mental health worldwide is concerning. This is a worldwide emergency, and there is an urgent need for research about this topic to prevent long-lasting adverse effects on the population. Unpreparedness and inconsistencies in guidelines, lockdowns, containment strategies, unemployment, financial losses, physical distancing, isolation, chaos, and uncertainty are among factors that lead to a rise in emotional distress, anxiety, and depression. Governments' decisions affect the socioeconomic status of a country and the psychological wellbeing of the people. COVID-19 pandemic exposed disparities in multiple mental health care systems by having adverse mental health effects in people with pre-existing mental health disorders and previously healthy individuals. Aggregation of concurrent or cumulative comorbid risk factors for COVID-19 disease and its psychosocial sequelae could provide invaluable information for the public health stakeholders. This review aims to address the burden and the psychosocial impact of the COVID-19 pandemic, the challenges and opportunities facing mental health systems and proposes new strategies to improve the mental health outcomes in the post-COVID era.